Physical activity in adults with controlled and uncontrolled asthma as compared to healthy adults: a cross‐sectional study. Issue 1 (15th January 2013) - Verlaet, Annelies; Moreira, Andre; Sá‐Sousa, Ana; Barros, Renata; Santos, Rute; Moreira, Pedro; Fonseca, Joao
Abstract: Background: Though exercise‐induced bronchoconstriction is common among asthmatics, physical activity (PA) seems important in asthma management. Still, various studies point at avoidance of sports and certain daily life activities like walking stairs, even by patients with mild symptoms. We aimed to compare physical activity levels between healthy subjects and asthmatics with controlled and uncontrolled disease. Methods: Data on asthma and PA were drawn from the Portuguese National Asthma Survey. The short telephone version of the International Physical Activity Questionnaire (IPAQ) was used to measure PA levels. Current asthma was defined as self‐reported asthma and at least one of these criteria: one or more asthma symptoms in the last twelve months, currently taking asthma medication or an asthma medical appointment in the previous twelve months. Controlled asthma was defined as a CARAT global score > 24 or a CARAT second factor score ≤ 16. Healthy subjects were defined as individuals without atopy, heart disease or any respiratory symptom. X 2 and Mann–Whitney/Kruskall‐Wallis tests were used to compare groups. Logistic regression analyses were performed to assess relations between asthma status and PA dimensions. Results: A total of 606 non‐asthmatics, 125 controlled and 78 uncontrolled asthmatic subjects were included. In both genders, overall PA level did not differ significantly between groups. Controlled (men) and uncontrolled (women) asthmatics did more vigorous PA than healthy respondents. Male controlled asthmatics also did more moderate PA. Crude logistic regression showed positive relations between daily sitting time, vigorous and moderate PA and controlled asthma in men and between vigorous PA and uncontrolled asthma in women. After adjustments for confounders, moderate PA remained a predictor of controlled asthma in men, while vigorous PA doubled the risk of uncontrolled asthma in women. Conclusion: Our study showed that adult asthmatics, independent of asthma control, do not seem to have a more sedentary lifestyle than their peers. Nevertheless, PA should be encouraged, as only about half of them reached activity recommendations.